Graphene geopolymeric cement and preparation method thereof - ZHANG GUOXUE; LU JUAN (2017)
The invention discloses graphene geopolymeric cement which is prepared from the following components in parts by weight: 100 parts of metakaolin, 10 parts of sodium hydroxide, 40 parts of sodium silicate, 30 parts of water, 0.6-1 part of a filler and 1-4 parts of a dispersing agent, wherein the filler comprises a PVA fiber; and the dispersing agent comprises graphene. According to the graphene geopolymeric cement, the compressive strength is 31-41MPa and the breaking strength is 4.2-6.2MPa. According to the graphene geopolymeric cement, metakaolin, sodium hydroxide, and water are taken as main raw materials of the geopolymeric cement, the graphene dispersing agent and the PVA fiber are added to the geopolymeric cement according to different quantities, so that the strength and the working performance are improved, and the graphene geopolymeric cement is taken as a 3D printing building material. 本发明公开了种石墨烯土聚水泥，包括按质量比计的偏高岭土100份、氢氧化钠10份、水玻璃40份、水30份、填充剂0.6～1份和分散剂1～4份，所述填充剂包括PVA纤维，所述分散剂包括石墨烯。其抗压强度为31～41MPa，抗折强度为4.